Implementation of Smoke Free Area Policy in Banda Aceh City: Analysis of the Concept of Collaborative Governance - Muazzinah, Muazzinah; Fuad Khalil, Zakki; Zamharira, Cut; Rahmah, Rauzatul (Iapa Proceedings Conference, 2023)
This study aims to examine the implementation of the No Smoking Area policy as stipulated in Qanun Kota Banda Aceh Number 5 of 2016. In an effort to improve the degree of public health, the government controls the dangers of cigarette smoke, of course through collaboration with various parties in the enforcement and implementation of the Smoke Free Area in Banda Aceh City. The purpose of this research is to find out the implementation of the Smoke Free Area policy through the concept in Banda Aceh City. This research uses a qualitative descriptive approach by analyzing Ansell and Gash's collaborative governance theory which includes face-to-face dialogue, trust between stakeholders, mutual commitment, sharing understanding and interim results. The results showed that the implementation of the No Smoking Area has not been running optimally, marked by low public awareness, sanctions that are not firm and socialization that has not been comprehensive. For this reason, it is expected from various parties, including the government, non-governmental organizations, the media, to intensify socialization and guidance to all levels of society in order to increase awareness of the importance of healthy living and smoke-free, community involvement in every activity and the need for strict sanctions so that policies run effectively